KAJIAN YURIDIS TENTANG PRAKTEK PERSAMAAN TERHADAP MEREK TERKENAL DITINJAU DARI UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS - G.M.I. Mamoribo, Margaretha (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This research was conducted with the aim of knowing the causes of certain business actors committing violations of well-known brands and to find out the law enforcement against violations of well-known brands reviewed from Law 20 of 2016 concerning Trademarks and Geographical Indications. In this research the author uses a normative juridical research method. Normative juridical is legal research of the literature conducted by examining library materials or secondary data. The results of this study reveal that the cause of certain business actors committing violations is because they have bad intentions and desire to obtain a large profit by means of breaking the law. Meanwhile, the legal protection provided for the well-known brand is carried out using 2 (two) methods, namely preventive legal protection and repressive legal protection. The Trademark Law protects well-known brands, where the trademark application will be rejected if it has similarities in principle or in whole with a well-known brand for similar goods and/or services. Legal protection of Well-known Trademark Rights in Indonesia is regulated by Law Number 20 of 2016 concerning Trademarks and Geographical Indications.